Influence of national competitiveness indicators on the export performance of the Visegrad Group Plus countries - Ingrid Majerová; Jan Nevima (DANUBE: Law, Economics and Social Issues Review, 2018)
A high level of competitiveness is the goal of every economic entity, whether individuals, companies, regions or nations. This paper discusses the issue of national competitiveness, which can be further divided into non-measurable and measurable input and output indicators. Output indicators are analysed in this paper, among which are a degree of openness, export performance, transformational performance and relative power of specialization. The aim is to find the relations among these indicators in the selected EU countries that form the Visegrad Group Plus, namely the Czech Republic, Slovakia, Hungary, Poland, Austria and Slovenia. These linkages have been tested by a panel regression model during the period 1995 to 2015. Strong impact of all indicators on export performance was assumed. However, this hypothesis was proved only partially, namely regarding the influence of openness degree and transformational performance on the export performance in period fixed effects.
Keywords: 330; Competitiveness; Determinants of Competitiveness; Panel Regression; Period and Cross Effects; Visegrad Group Plus